Implementing mental health in practice : strategies to engage patients and families. Social emotional problems in children birth to 5 - Bauer, Nerissa S.; American Academy of Pediatrics ([Elk Grove Village, Illinois] : American Academy of Pediatrics, 2015)
This video focuses on using motivational interviewing techniques to identify and address social emotional problems in children birth to 5. In the case demonstrated, a couple comes into the office with their 24-month-old daughter. The child sits quietly throughout the appointment. You are concerned because she initiates no eye contact with her parents, and the parents do not engage with her. She doesn't vocalize or smile, even when you try to engage with her. Her parents do not express concern about this. They say "she's a good kid, cries very little and likes to entertain herself". They describe that their Early Head Start teacher has said she is very quiet, shows little emotion, and does not seem to have a preference for any of the caregivers (or does not mind who holds her, even new volunteers). There are no concerns about her physical health and she appears to be growing well.
Presenter: Nerissa S. Bauer.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed October 19, 2020)
Keywords: Emotional problems of children; Problem children -- Functional assessment; Behavior disorders in children; Documentary films; Educational films; Nonfiction films; Internet videos; Streaming video; Short films